E-Government sebagai Bentuk Inovasi Pemerintah Daerah untuk Peningkatan Kualitas Pelayanan Publik - Anjani, Anjani; Malawat, Sitna Hajar (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The development of technology and communication is increasingly advanced and rapid, knowingly or unknowingly it has its own impact on people's lifestyles and the current pattern of government work. In the past, there was a distance between the government and the people. But now, with increasingly advanced technological developments between the government and the people it seems as if there is no distance anymore. Then, the current public service paradigm considers recipients of public services as citizens so that there is no difference in terms of social status, ethnicity, race or religion. These changes make local governments inevitably have to innovate to provide the best service to the community.